2002
DOI: 10.1046/j.1440-1827.2002.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of integrin β‐4 in papillary thyroid carcinoma with gross lymph node metastasis

Abstract: Although the prognosis is generally good for patients with papillary thyroid carcinoma, gross nodal metastasis of carcinoma has a poor prognosis. It is necessary to clarify how carcinoma progresses to gross nodal metastasis in order to establish a cure. The adhesion molecule integrin beta-4 is considered to be related to cell migration and metastasis in many carcinomas. In the present study, we examined integrin beta-4 expression in 65 cases of human papillary thyroid carcinoma using immunohistochemical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…12 Furthermore, the potential role of the a6b4 integrin in metastasis is supported by studies in papillary thyroid carcinoma which suggested that the increased expression of the integrin b4 subunit in cancer lesions could play a role in the development of lymph node metastasis. 27 Certainly, the in vivo data coupled with extensive in vitro data suggest that the a6b4 is associated with the invasiveness and metastatic potential of late stage cancers. 16,[24][25][26][27] In our study, the six pancreatic adenocarcinoma cases that were associated with lymph node metastasis displayed overexpression of the integrin b4 subunit in cancer cells (Figure 1i-j).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, the potential role of the a6b4 integrin in metastasis is supported by studies in papillary thyroid carcinoma which suggested that the increased expression of the integrin b4 subunit in cancer lesions could play a role in the development of lymph node metastasis. 27 Certainly, the in vivo data coupled with extensive in vitro data suggest that the a6b4 is associated with the invasiveness and metastatic potential of late stage cancers. 16,[24][25][26][27] In our study, the six pancreatic adenocarcinoma cases that were associated with lymph node metastasis displayed overexpression of the integrin b4 subunit in cancer cells (Figure 1i-j).…”
Section: Discussionmentioning
confidence: 99%
“…27 Certainly, the in vivo data coupled with extensive in vitro data suggest that the a6b4 is associated with the invasiveness and metastatic potential of late stage cancers. 16,[24][25][26][27] In our study, the six pancreatic adenocarcinoma cases that were associated with lymph node metastasis displayed overexpression of the integrin b4 subunit in cancer cells (Figure 1i-j). When pancreatic cells were found invading the peripheral nerves, the invading cancer cells also overexpressed integrin a6b4.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Prior reports indicate that ITGB4 is upregulated in multiple tumor types, including pancreatic cancer. 8 In several cancers, high levels of ITGB4 expression have been linked to poor prognosis or aggressive behavior, [12][13][14][15][16] but the clinicopathological significance of ITGB4 overexpression in PDA remains unclear. The aim of the current study was to clarify the clinicopathological significance of ITGB4 overexpression in PDA and to suggest the potential function of ITGB4 in cancer EMT.…”
mentioning
confidence: 99%
“…Integrin-␤4 complexes only with integrin-␣6 and is recognized as important for the formation of epithelial hemidesmosomes and is relevant to cancer biology. Increased integrin-␤4 expression is linked to increased tumor invasiveness in squamous cell carcinomas (26) and papillary carcinomas of the thyroid (14) and portends a poor prognosis in both breast (24) and bladder cancer (10). Until recently, however, little was known about the role of integrin-␤4 in normal EC physiology.…”
mentioning
confidence: 99%